Turkish EFL teachers' opinions on intercultural approach in foreign language education - (:unkn) unknown (ELSEVIER SCIENCE BV, 2009)
In recent years there has been a growing interest in the cultural dimension of foreign language education and teachers today are expected to promote the acquisition of intercultural competence in their learners (Byram & Zarate, 1997). The present study aims to investigate how well informed and equipped Turkish teachers of English are in terms of adding the intercultural aspect into their language teaching and to determine their attitudes to this issue, thereby complementing similar studies carried out in other countries. Data were collected from 200 EFL teachers by means of a questionnaire and analyzed by means of quantitative methods. (C) 2009 Elsevier Ltd. All rights reserved
Keywords: Intercultural competence; teacher attitudes